2015
DOI: 10.1139/cjpp-2014-0361
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between endoplasmic/sarcoplasmic reticulum stress (ER/SR stress), mitochondrial signaling and Ca2+ regulation in airway smooth muscle (ASM)

Abstract: Airway inflammation is a key aspect of diseases such as asthma. Several inflammatory cytokines (e.g., TNFα and IL-13) increase cytosolic Ca2+ ([Ca2+]cyt) responses to agonist stimulation and Ca2+ sensitivity of force generation, thereby enhancing airway smooth muscle (ASM) contractility (hyper-reactive state). Inflammation also induces ASM proliferation and remodeling (synthetic state). In normal ASM, the transient elevation of [Ca2+]cyt induced by agonists leads to a transient increase in mitochondrial Ca2+ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 163 publications
(239 reference statements)
2
45
0
Order By: Relevance
“…To assess the extent of filamentous versus fragmented morphometry, the form factor (an index of mitochondrial branching) and aspect ratio (an index of mitochondrial branch length) were calculated for each cell using a custom-written MATLAB (The MathWorks)-based program (36,37). A decrease in aspect ratio and/or form factor indicates mitochondrial fragmentation (33)(34)(35)(36)(37).…”
Section: Construction Of Vdr Pegfp Expression Vectors and Transfectiomentioning
confidence: 99%
“…To assess the extent of filamentous versus fragmented morphometry, the form factor (an index of mitochondrial branching) and aspect ratio (an index of mitochondrial branch length) were calculated for each cell using a custom-written MATLAB (The MathWorks)-based program (36,37). A decrease in aspect ratio and/or form factor indicates mitochondrial fragmentation (33)(34)(35)(36)(37).…”
Section: Construction Of Vdr Pegfp Expression Vectors and Transfectiomentioning
confidence: 99%
“…269026, containing 35 endotoxin units/mg, normalized to protein content; GREER, Lenoir, NC) extract suspended in PBS through intranasal administration on day 1 and boosted again on day 8. Mice were then administered 25 g of HDM consecutively on days [15][16][17][18][19] 1A, 5A, and 9A). Another set of mice received two additional doses of HDM on days 25 and 27 (see Fig.…”
Section: Animalsmentioning
confidence: 99%
“…In turn, ER stress activates the unfolded protein response, resulting in the activation of downstream signaling pathways to restore ER homeostasis (10,11). Furthermore, ER stress plays a critical role in several inflammatory disease conditions, including airway inflammation, chronic airway disorders, and remodeling (9,15,25,33,34,51).…”
mentioning
confidence: 99%
“…Its signaling promotes the differentiation of goblet cells. IL-13 severely impairs mucus transport by airway epithelial cells (Tyner et al, 2006, Yan et al, 2014, Bonser et al, 2016)and induces ROS formation and ER stress in airway smooth muscle (Delmotte and Sieck, 2015). Consistent with previous results showing an increase in IL-13 in the lungs of mice exposed to OVA, we found that Lyn and 4-PBA suppressed IL-13 in mice exposed to OVA (Fig.…”
Section: Resultsmentioning
confidence: 99%